International orientation and technological diffusion among SMEs in ASEAN - Alinsunurin, Jason P. (Animo Repository, 2011)
Entrepreneurial activity has wide and persistent variations across economies in terms of their performance on international market reach. This paper aims to empirically estimate the effects of technology adoption and diffusion to the international orientation of SMEs, which we proxied by the proportion of SMEs’ customers living abroad. Utilizing the Global Entrepreneurship Monitor (GEM) data, our estimates show that owner-managers adopting a technology which are less one year old have significantly higher odds of having more customers living abroad, than those who adopted later technologies. Male owner-managers have higher levels of international orientation, with younger owner-managers having slightly higher odds of breaking into international markets. Our estimates also show that ownership and experience are powerful determinants of international orientation. Within Asean, owner-managers in Thailand, Malaysia, Indonesia and the Philippines have lower odds of breaking and increasing their levels of access to international markets as compared to other economies covered by the GEM survey.